Mean-reverting behavior of current account in Asian countries - Lau, Evan; Ahmad Zubaidi, Baharumshah (Elsevier B.V., 2005)
This paper adopted the series specific panel unit root test of Breuer et al. [Oxford Bullet in of Economics and Statistics 64 (2002, SURADF) 527–546] to test for the mean-reverting behavior of current account for the panel of twelve Asian countries. The results illustrate that the current account s in these countries are a mixture of I(0) and I(1) process and the commonly used panel root tests could lead to misleading inferences.